Sikap Dan Persepsi Konsumen Terhadap Merek Jilbab Syafirah Muslimah Di Tangerang Selatan: Pendekatan Semantic Differential - M. Yasin Alatas; Mursalin Mursalin; Andriasnyah Andriasnyah; Andri Prasetyo; Dwi Hardianto; Roosita Meilani Dewi (Indonesian Journal of Economics Application (IJEA), 2018)
The application of semantic differential method has been much done to examine consumer behavior. In this article, these methods also will be used in studying consumer behavior on hijab of Syafirah Muslimah in South Tangerang. Syafirah Muslimah is an SME that are developed enough in producing the hijab. The results of showed that the consumer gives good perception to its brand. It is guaranteed because the products including affordable. Policy implications that can be followed-up is to do implementing intensive promotion to consumers.